The Efficacy of Laser Therapy for Rotator Cuff Tendinopathy: A Systematic Review and Meta-Analysis - Jennifer Boudreault; François Desmeules; Jean-Sébastien Roy; Clermont E Dionne; Pierre Frémont; Joy C MacDermid (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2016)
Objective: To perform a systematic review and meta-analysis on the efficacy of laser therapy (LT) for rotator cuff (RC) tendinopathy in adults. Methods: A literature search was conducted in four databases for randomized controlled trials (RCTs) published until May 2014, comparing the efficacy of LT to any other intervention. RCTs' characteristics were extracted using a standardized form and the risk of bias was evaluated using the Cochrane Risk of Bias tool. Data were summarized qualitatively or quantitatively (meta-analysis). Results: Thirteen RCTs, with moderate mean methodological score (66.4%± 10.0), were included. It was concluded that LT may provide short-term pain relief of minimally significant clinical importance compared to placebo (sham LT), ultrasound therapy, or clinical recommendations alone. In terms of self-reported function and shoulder range of motion (ROM), evidence was inconclusive. When compared to an exercise program, LT was not deemed to have superior effects on pain, function or shoulder ROM. LT in conjunction with exercise was not superior to exercise alone with respect to pain, function and shoulder ROM.  Conclusion: Low to moderate grade evidence supports that LT may reduce pain in the short term in adults with RC tendinopathy, while its effects on function and ROM are not supported. Until more high quality evidence demonstrates clearly the efficacy of LT, clinicians should use LT cautiously and in the sole objective of alleviating pain in the short-term.